Two Adjacent and Similar TetR Family Transcriptional Regulator Genes, SAV577 and SAV576, Co-Regulate Avermectin Production in Streptomyces avermitilis - Guo, Jia; Zhang, Xuan; Chen, Zhi; Wen, Ying; Li, Jilun (PLOS ONE, 2014)
Streptomyces avermitilis is an important bacterial species used for industrial production of avermectins, a family of broad-spectrum anthelmintic agents. We previously identified the protein SAV576, a TetR family transcriptional regulator (TFR), as a downregulator of avermectin biosynthesis that acts by controlling transcription of its major target gene SAV575 (which encodes cytochrome P450/NADPH-ferrihemoprotein reductase) and ave genes. SAV577, another TFR gene, encodes a SAV577 protein that displays high amino acid homology with SAV576. In this study, we examined the effect of SAV577 on avermectin production and the relationships between SAV576 and SAV577. SAV577 downregulated avermectin biosynthesis indirectly, similarly to SAV576. SAV576 and SAV577 both directly repressed SAV575 transcription, and reciprocally repressed each other's expression. SAV575 transcription levels in various S. avermitilis strains were correlated with avermectin production levels. DNase I footprinting and electrophoretic mobility shift assays indicated that SAV576 and SAV577 compete for the same binding regions, and that DNA-binding affinity of SAV576 is much stronger than that of SAV577. GST pull-down assays revealed no direct interaction between the two proteins. Taken together, these findings suggest that SAV577 regulates avermectin production in S. avermitilis by a mechanism similar to that of SAV576, and that the role of SAV576 is dominant over that of SAV577. This is the first report of two adjacent and similar TFR genes that co-regulate antibiotic production in Streptomyces.